Sebuah tudi Empiris tentang Strategi Keberlanjutan pada Usaha Pengolahan Ikan yang Dipimpin oleh Perempuan di Pesisir Pantai Depok, Kabupaten Bantul - Ayu Kumala Sari; Zulfa Nur Auliatun Nissa'; Miftahul Ajri; Ali Hasyim Al Rosyid (Jurnal Ilmu Sosial dan Humaniora, 2024)
This study explores sustainability strategies for women’s fish processing businesses in Depok, Bantul Regency, where economic conditions remain underdeveloped despite Indonesia’s vast coastal potential. Women fish processors face constraints in accessing technology, markets, and capital. The research aims to develop sustainable adaptation strategies to strengthen their resilience amid social, economic, and environmental challenges. A mixed-methods approach was used, surveying 75 women fish processors, supplemented by interviews, observations, and document reviews. Internal and external factors were analyzed through IFE and EFE matrices, while IE and SWOT analyses helped identify strategic alternatives. The women's fish processing businesses were positioned in cell V of the IE matrix, indicating a "Hold and Maintain" strategy, with an IFE score of 2.01 and an EFE score of 2.43. The recommended strategies include market penetration and product development. Despite strengths in product variety and competitive pricing, the businesses struggle with unstable raw material supplies. Key strategies for sustainability emphasize market expansion, product development, and strengthening external networks. Social capital—particularly norms, cooperation, and trust—plays a significant role in business growth. Norms received the highest score (1.95), followed by trust (1.62) and networks (1.48), highlighting strong social cohesion but a need for improved network development to access resources and markets. These strategies have crucial implications for the long-term sustainability of women’s fish processing businesses, underscoring the importance of diversifying products and building stronger networks to ensure more stable and profitable operations.